LOGIQUES CONFLICTUELLES DE GESTION DES ESPACES PUBLICS URBAINS EN CONTEXTE POST-CONFLIT : L’EXEMPLE DE BOUAKÉ (CÔTE D’IVOIRE) - Kra, Kouamé Walter (European Scientific Journal, ESJ, 2015)
From an urban sanitation operation led in a post-crisis context in Bouaké an ivorian medium size town, the paper examines the conflicting interactions between two state institutions respectively responsible for the operation (Anasur) and management public domain (town hall). This intraconflictual relationship was to challenge the control of public spaces to sanitize, but with different aims. A qualitative analysis inspired by the real conflict theory has shown that the conflict between antagonists institutions is built on both the chaotic management of the city inherited from the rebellion, on the need to mobilize emergency resources to ensure operation of municipal services including the exploitation of residues of that chaotic management and, paradoxically at the same time, on the willingness of the state to regain control of the public spaces of Bouaké in its economic policy.